Legal Protection for Patients and Providers Telemedicine Services: Perspectives Principle Balance - Helana, Ricky; Setiadi, Edi; Januarita, Ratna; Erlena, Erlena (Journal La Sociale, 2025)
Development technology No only change pattern life public everyday, but also influential in various industry, including in service known health with Telemedicine Services health through telemedicine has Lots benefits, but also risks high, so that required protection law for doctor and patient in service health through telemedicine as digital transformation. Objective from study This mapping and testing existing rules and regulations regarding digital transformation in particular For telemedicine, is it is already optimal in fulfil its function as service health to society, and is also associated with principle balance as outlined in Health Law No. 17 of 2023 Concerning Health. Methods the approach used is legal normative, with specification study nature descriptive analytical. The data used studies literature using secondary and tertiary data with technique analysis qualitative normative. Based on results study This show that; regulation protection law for doctor and patient in service health through telemedicine not yet based on principle balance. Invite law temeledicine regulated in Law No. 17 of 2023 concerning Health is still Not yet explain guidelines in detail about implementation telemedicine.